Antibiotics Resistance Level of Vibrio spp. Isolated From Northern Bali Area - Dewi, Widya Purnama; Julyantoro, Pande Gde Sasmita; Kartika, I Wayan Darya (Advances in Tropical Biodiversity and Environmental Sciences, 2020)
One conventional method that usually done when the organism infected by pathogenic bacteria is using antibiotics, either with single or combination usage. However, the misuse of antibiotics dosages leads to resistance development of pathogenic bacteria. This study aims to determine the antibiotic resistance level of Vibrio spp. which was isolated from the waters of North Bali and to investigate the difference of resistance level between Vibrio spp. isolated from the cultivation area and outside the cultivation area. This research was conducted at the Microbiology Laboratory of BKIPM Denpasar and the Laboratory of Fisheries at the Faculty of Marine Science and Fisheries, Udayana University from November 2019 to February 2020. Antibiotic tests were carried out in vitro using 8 types of antibiotics namely tetracycline, oxytetracycline, enrofloxacin, ciprofloxacin, amoxycillin, doxycycline, ampicillin, and erythromycin with different concentrations of 0.5, 1, 2, 4, 8, 16, 32, 64, 64, 128, 256 and 512 ppm. and this test was carried out using a microplate reader to obtain absorbance values before and after incubation to determine the level of resistance of isolated Vibrios. The research showed that overall minimum inhibitory concentration (MIC) of Vibrio was below 100 ppm while the Vibrio spp. isolated from cultivation area have higher resistance level compared to outside cultivation area.